Differential transcriptional response to antibiotics by Pseudomonas putida DOT-T1E - Molina-Santiago, Carlos; Daddaoua, Abdelali; Gómez-Lozano, María; Udaondo, Zulema; Molin, Soren; Ramos, Juan-Luis (Wiley, 2015)
Multi-drug resistant bacteria are a major threat to humanity, especially because the current battery of known antibiotics is not sufficient to combat infections produced by these microbes. Therefore, the study of how current antibiotics act and how bacteria defend themselves against antibiotics is of critical importance. Pseudomonas putida DOT-T1E exhibits an impressive array of RND efflux pumps, which confer this microorganism high resistance to organic solvents and antibiotics that would kill most other microorganisms. We have chosen DOT-T1E as a model microbe to study the microbial responses to a wide battery of antibiotics (chloramphenicol, rifampicin, tetracycline, ciprofloxacin, ampicillin, kanamycin, spectinomycin and gentamicin). Ribonucleic acid sequencing (RNA)-seq analyses revealed that each antibiotic provokes a unique transcriptional response profile in DOT-T1E. While many of the genes identified were related to known antibiotic targets, others were unrelated or encoded hypothetical proteins. These results indicate that our knowledge of antibiotic resistance mechanisms is still partial. We also identified 138 new small RNAs (sRNAs) in DOT-T1E, dramatically adding to the 16 that have been previously described. Importantly, our results reveal that a correlation exists between the expression of messenger RNA and sRNA, indicating that some of these sRNAs are likely involved in fine tuning the expression of antibiotic resistance genes.
Keywords: Pseudomonas; Antibióticos; Transcriptomics; Antibiotics